TTHE ATTITUDE OF THE SOCIETY TOWARDS INCURABLE CHILDREN: HISTORICAL AND CULTURAL ANALYSIS - G. L. Mikirtichan (Вопросы современной педиатрии)
This article is an attempt to study the attitude towards the incurable child in different societies throughout the history. The attitude depended on the level of socio-economic development of the society, type and form of the institutionalization of the family and family relations, social, historical and cultural peculiarities of the nature and ierarchy of parental values, on the perception of childhood as a sociocultural phenomena, on existing juridical system, that defines parental and child rights, and on the level of healthcare system development, including pediatrics.